The effect of pre-admission immunosuppression on colectomy rates in acute severe ulcerative colitis. (November 2018) - Patrick, Desmond; Doecke, James; Irwin, James; Hanigan, Katherine; Simms, Lisa; Howlett, Mariko; Radford-Smith, Graham
Background: Patients on immunosuppression at the time of acute severe ulcerative colitis have been suggested to be at a higher risk of colectomy than those who are treatment-naïve. The aim of this study was to examine the effect of immunosuppressive therapy on the risk of colectomy. Method: We conducted a retrospective observational cohort study using prospective data examining the 30 day and 1 year colectomy rates of 200 consecutive patients with an index episode of acute severe ulcerative colitis as defined by the Truelove and Witts criteria. Results: Immunosuppression on admission was shown not to increase colectomy rate at 30 days post-admission (immunomodulator: p = 0.422, oral steroids: p = 0.555). A total of 24 patients underwent colectomy between 30 days and 1 year. A three-fold higher risk of colectomy at 1 year was seen in those requiring an immunomodulator prior to the index admission compared with those started de novo during the index admission [41% versus 14% odds ratio (OR): 2.93 (1.19–7.24 p = 0.016)]. Factors most predictive of colectomy at 30 days were abdominal radiographic colonic dilation ⩾5.5 cm, first presentation of ulcerative colitis, C-reactive protein ⩾ 45 mg/l on day 3 of therapy and bowel frequency ⩾8 on day 3. Conclusion: The need for an immunomodulator prior to admission with acute severe ulcerative colitis increases the medium-term colectomy rate by three-fold at 1 year. Prospective studies are needed to confirm these findings and develop strategies to reduce the high risk in this subgroup of patients.